A LABORATORY STUDY TO IMPROVE ACID STIMULATION IN SANDSTONES - Septi Anggraeni; Junita Trivianty; Bambang Widarsono (Testing Center for Oil and Gas LEMIGAS, 2006)
The main purpose of acidizing is to improve well productivity. Acids are useful for this reason because of their ability to dissolve undesired formation minerals and materials which may either be intrinsic in nature or be introduced into the formation during the processes of drilling, completion, and production. The effectiveness of acids in improving productivity in a particular well essentially depends on an accurate analysis of the problem and the selection of acid.Prudent judgment in acid to be used should be confirmed by laboratory tests. Apart from the analysis on the nature of the formation damage itself, acid selection should be based on study of reservoir rocks mineralogy and characteristics in general and accordingly the relevant material/minerals to be dissolved or removed. Improper diagnostics may result in inefficient, and even damaging, acidizing. Various studies have been conducted in this highlight (e.g. Crowe, 1984; Gidley, 1971; Crowe in Economides and Nolte, 1989; Daccord in Economides and Nolte, 1989; Ali, 1981; and Piot and Perthuis in Economides and Nolte, 1984).Those studies conducted in the past reveal that in comparison the success ratio of acidizing for limestone reservoir is almost 90%, whereas for sandstone reservoir the success ratio is only 30%. Undoubtedly, this disparity in success ratios is caused by the fact that appropriate acids dissolve limestones more properly due to limestones generally simpler mineral composition and by the fact that sandstones usually have more complex mineralogy hence providing less simple materials to dissolve. From this point Those studies conducted in the past reveal that in comparison the success ratio of acidizing for limestone reservoir is almost 90%, whereas for sandstone reservoir the success ratio is only 30%. Undoubtedly, this disparity in success ratios is caused by the fact that appropriate acids dissolve limestones more properly due to limestones generally simpler mineral composition and by the fact that sandstones usually have more complex mineralogy hence providing less simple materials to dissolve. From this point